A utilização do Scratch no ensino de geometria plana - CUNHA, José Martins da (2022)
We live in an increasingly technological world and during the pandemic period of covid-19, the use of technologies was intensified in education so that teaching does not stop in the period of social isolation. Practically all teachers had to invent themselves, teaching their classes via meet, which requires a lot of use of the internet and innovative technological teaching tools. In this way, several online courses took place during the pandemic, but few had the opportunity to do them due to lack of internet. One of them was about Scratch, to know how to program, which for this work was adapted for mathematics in the construction of some flat figures, such as: square, rectangle, triangle, etc., so that the teacher can have a suggestion to apply in 7th grade classes. elementary School. We chose to work on mathematics using Scratch, as elementary school teachers in Tomé-Açu/Pa have little knowledge. In this way, the present article was built through bibliographic research that aims to present this tool to teachers and students of public schools in Tomé-Açu, but which unfortunately cannot yet be carried out, due to several factors that are highlighted in the development of the work, but that in the not-so-distant future he intends to apply it so that there is a better quality in teaching, in Tomé-Açu, which is still very lacking in the use of technologies.